Code Switching and Code Mixing Practised By K-POP Idols Diaspora - muhartoyo, muhartoyo; Sharone, Vanesha (Bina Nusantara University, 2023)
The research discussed K-pop idols as ambassadors for brands, contributing to the global popularity of K-pop as a cultural phenomenon. Given their strong influence and popularity, it was fascinating to discern how K-Pop idols' diaspora communicates with each other. By using the descriptive-qualitative approach with the interpretive-explorative pattern, the research was intended to examine the practice of code-switching and code-mixing by K-pop idols' diaspora during their interaction, to enumerate the code-switching and code-mixing instances, as well as to study the reasons/motivations behind the use of using code-switching and code-mixing. The result of the data analysis confirmed that, like other bilinguals, K-Pop idol's diaspora utilize code switching and code mixing during their interaction for various underlying reasons. It is found that there are 19 inter-sentential switchings, 18 intra-sentential switching, four tag switching, 11 insertion code-mixing, four alternation code-mixing, and six congruent lexicalizations with different reasons or motivations. The research concluded that it is almost inevitable for bilinguals and multilinguals to practice code- switching and code-mixing to navigate language selection during their interaction.